2021
DOI: 10.1021/acs.nanolett.0c04048
|View full text |Cite
|
Sign up to set email alerts
|

Moiré Superlattice-Induced Superconductivity in One-Unit-Cell FeTe

Abstract: In this work, we demonstrate that the nonsuperconducting single-layer FeTe can become superconducting when its structure is properly tuned by epitaxially growing it on Bi 2 Te 3 thin films. The properties of the single-layer FeTe deviate strongly from its bulk counterpart, as evidenced by the emergence of a large superconductivity gap (3.3 meV) and an apparent 8 × 2 superlattice (SL). Our first-principles calculations indicate that the 8 × 2 SL and the emergence of the novel superconducting phase are essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…One possibility is the charge transfer effect, which was believed to induce the interfacial superconductivity in Bi 2 Te 3 /FeTe. , The difference in band alignment of FeSe vs FeTe relative to Bi 2 Te 3 could lead to widely varying charge transfer to and from the TI layer (see Supporting Information Figures S5 and S6), possibly shifting the superconducting dome on the phase diagram until completely suppressing superconductivity in FeSe while enhancing it in FeTe. The complete removal of excess Fe in our samples, as can be seen from the RBS results in Table S1, could be another possible reason for the emergence of superconductivity in FeTe since it has been reported that excess Fe is deleterious for the superconductivity in both FTS bulk crystals and TI/FeTe films. , A structural effect at the interface could also help develop the superconductivity, as proposed in a recent scanning tunneling microscopy (STM) study of a monolayer FeTe film grown on Bi 2 Te 3 . However, neither of these two mechanisms can explain the absence of superconductivity in Se-rich samples.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…One possibility is the charge transfer effect, which was believed to induce the interfacial superconductivity in Bi 2 Te 3 /FeTe. , The difference in band alignment of FeSe vs FeTe relative to Bi 2 Te 3 could lead to widely varying charge transfer to and from the TI layer (see Supporting Information Figures S5 and S6), possibly shifting the superconducting dome on the phase diagram until completely suppressing superconductivity in FeSe while enhancing it in FeTe. The complete removal of excess Fe in our samples, as can be seen from the RBS results in Table S1, could be another possible reason for the emergence of superconductivity in FeTe since it has been reported that excess Fe is deleterious for the superconductivity in both FTS bulk crystals and TI/FeTe films. , A structural effect at the interface could also help develop the superconductivity, as proposed in a recent scanning tunneling microscopy (STM) study of a monolayer FeTe film grown on Bi 2 Te 3 . However, neither of these two mechanisms can explain the absence of superconductivity in Se-rich samples.…”
mentioning
confidence: 73%
“…However, the growth of heterostructure with mixed symmetries are challenging and only be realized in limited cases of elemental metals 35,36 or in the monolayer-limit. [37][38][39] So far, no synthesis route to grow an epitaxial and macroscopically contiguous SC layer on a TI has been identified for FTS as well as for any other chalcogenide superconductors.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…15−21 Recently, however, it was discovered that superconducting FTS films can be epitaxially grown on a threefold topological insulator material, Bi 2 Te 3 , due to the rare uniaxial lattice match between FTS and Bi 2 Te 3 , a growth mode dubbed "hybrid symmetry epitaxy". 22,23 Here, we show that the similar hybrid symmetry epitaxy mode allows FTS to grow epitaxially on a sixfold MnTe layer. It is notable that MnTe is an antiferromagnetic (AFM) insulator with a Neél temperature of ∼310 K and plays an important role in the recently discovered intrinsic magnetic topological insulator family (MnTe) m (Bi 2 Te 3 ) n .…”
mentioning
confidence: 74%